The wearing of Christian baptismal crosses (Stato, Chiese e pluralismo confessionale, 2012)
The text, accepted by the Director, reproduces the joint Conclusion by the Representation of the Russian Orthodox Church to the Council of Europe (Strasbourg, France) and the Institute for State-Confessional Relations and Law (Moscow, Russia)SUMMARY: 1. On the religious significance of baptismal crosses and grounds for the need for Orthodox Christian believers to wear them – 2. On the illegitimate nature of the ban imposed by the state on the wearing of baptismal symbols of Christian religious affiliation – 3. Absence of any grounds for assessing the religious rite of wearing Christian baptismal crosses as a threat to public safety, public order, health or morals or the rights and freedoms of others – 4. The groundless emasculation, denial and reduction of the religious meaning and importance of Christian baptismal crosses.